The Effect of the Arctic Ozone Depletion Observed at Tsukada, Japan in February 2001 (Extended Abstract) - Murata, Isao; Kobayashi, Nobutaka; Nakane, Hideaki; Fukunishi, Hiroshi (Faculty of Science, Tohoku University, 2003)
application/pdf 紀要類 (bulletin) 462465 bytes departmental bulletin paper